Analyzing factors affecting the adoption of cloud computing: a structural equation modeling approach - Arı, Ezgi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Cloud computing is a new and upcoming technology in Turkey. It is also a new business model for companies. Companies begin to invest in cloud computing with the expectation that this new technology will improve their business performance and operations. Cloud computing enables companies to buy their technological needs what if it is needed and they only pay for the amount that they used. However, many companies are not so much aware of its advantages and disadvantages clearly. The aim of the study is analyzing factors affecting the adoption of cloud computing and applying structural equation modeling technique. There are many factors that affect the adoption of cloud computing. This study examines previous studies related to cloud computing adoption and presents a new model and new factors according to both literature and expert interviews. In addition, structural equation modeling is applied to analyze interrelationships between the factors in the proposed model. According to study findings, need, on demand service, legislation and regulations, other factors (reliability, virtualization, maintenance, and performance) are have positive direct effects on cloud computing adoption. However, cost has negative direct effect on cloud computing adoption. On demand service, other factors, and security have positive direct effects on cost. Lastly, other factors and legislation and regulations have positive direct effects on security. According to results, the significance of supplier availability on cloud computing adoption and the significance of security on cost are not supported.
Keywords: Cloud computing.